Pengaruh Praktik Kesadaran Digital terhadap Pengurangan Stres dan Prestasi Akademik Mahasiswa Pendidikan Biologi - Rahmi Saputri; Hery Fajeriadi (Biocaster : Jurnal Kajian Biologi, 2026)
The development of digital technology in the world has increased the ease of access to education. However, it also creates new challenges that affect stress levels and academic achievement. This study focuses on analyzing the influence of digital mindfulness techniques on the level of stress experienced by students of the Department of Biology Education at Lambung Mangkurat University, as well as their academic achievements. A descriptive-exploratory method with a qualitative research approach was applied in this study. Data was collected through an online survey filled out by 71 students and 5 lecturers, as well as interviews with 9 students from various generations. Data analysis was carried out using a descriptive method, based on students' views and experiences. The results show that most students experience moderate to high levels of academic stress, especially due to multitasking on digital platforms and high academic expectations. Nonetheless, the application of digital awareness techniques contributes to more effective time management and improved ability to concentrate. This research highlights that digital awareness is essential to maintain a balance between technology use and students' mental health. Scientifically, the results of this study show the importance of digital awareness in biology education for adaptive, healthy, and sustainable learning.